2021
DOI: 10.1177/03400352211048914
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of health information literacy among women in rural Lake Zone, Tanzania

Abstract: This article presents the results from a descriptive cross-sectional survey that was conducted to assess the health information literacy skills of women of childbearing age in rural Lake Zone, Tanzania. A total of 349 women were involved in the study. The study found that most rural women in the study area have low levels of health information literacy. The aggregate scores of health information literacy indicate a mean of 42.86% with a normal distribution curve, and estimated close-to-zero skewness (0.172) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Understandably, access to reliable and credible health information is essential in helping people to make health-related decisions that will lead to positive health outcomes (Ghorbanian Zolbin et al, 2022;Kassim & Ndumbaro, 2021;Soleymani et al, 2021). Bearing this in mind, the janitors in this study expressed the need to be provided with this crucial information and information on how they can be registered to health insurance schemes to help them protect their health both at work and in times of crises such as that of COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…Understandably, access to reliable and credible health information is essential in helping people to make health-related decisions that will lead to positive health outcomes (Ghorbanian Zolbin et al, 2022;Kassim & Ndumbaro, 2021;Soleymani et al, 2021). Bearing this in mind, the janitors in this study expressed the need to be provided with this crucial information and information on how they can be registered to health insurance schemes to help them protect their health both at work and in times of crises such as that of COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…Maternal health information entails essential information that assists women in making decisions on their pregnancy care, preparation for delivery, and post-delivery care [ 7 ]. Access to and use of maternal health information is critical to women of childbearing age as it can affect women’s health during pregnancy, childbirth, and the care of newborns ([ [7] , [8] , [9] ]). Although access to and use of maternal health is important for pregnant women and newborns [ 10 ], observed that health information becomes useful when the users are able to comprehend the health information they have accessed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pregnant women with stable incomes and occupations tend to have wider access to resources and can better comprehend health information. The literature reviewed revealed that most studies conducted in Tanzania on maternal health information have little documentation on pregnant women's comprehension of maternal health information ([ [7] , [8] , [9] , 15 ]). In fact, none of the studies has researched the influence of socio-demographic characteristics on pregnant women's understanding of maternal health information, particularly in the Coastal region.…”
Section: Introductionmentioning
confidence: 99%